Theoretical and practical bases of work on the portrait in oil painting as the basis of mastering the professional and creative knowledge - Mishurovsky, V.V. (Pedagogy of Higher and Secondary Education, 2009)
The article describes the ways of formation of theoretical and practical bases of work on the portrait.